Resultados comparativos de diseño de mezclas de concreto con agregados de los ríos Cumbaza y Huallega - Meléndez Ganoza, Roger (1996)
The present research was conducted using aggregates Next quarries: RIO Cumbaza 150 m. Upstream of the bridge on the Marginal highway. Huallaga River: In the District of Shapaja, distant approximately 23 km. of the city ​​of Tarapoto. In the quarry of the river Cumbaza took samples were mixed of both thin thickness of Como in Concrete form, in an amount of 2,500 kg. and laboratory separated By sieving. In the quarry of the Huallaga river Samples were taken separately because that just So they do find in the riverbed in the following: Quantities 100 kg fine aggregate. " 1,200 kg coarse aggregate. These samples Were taken to the Laboratory of Soil Mechanics, Concrete and Asphalt Department of Civil Construction I.S.T. "Nor Oriental Jungle" bring paragraph Just I Work, with the advice of the Technical Civil Construction Velarde Pezo Perea (Professor and Head of Laboratory). One part of paragraph Samples were analyzed FIND The physical characteristics of the aggregates product of which was dismissed How to use the Added Fino del Huallaga River, as its fineness modulus = 0,46 does not make it suitable for use in Concretos. Perform the tests was determined as follows: FINE AGGREGATE River Cumbaza COARSE AGGREGATE: River Cumbaza Test No. 1: Fe = 175 kg / cm2 Test No. 2: Fe = 210 kg / cm2 FINE AGGREGATE River Cumbaza COARSE AGGREGATE: Huallaga River Test No. 3: Fe = 175 kg / cm2 Test # 4: Fe = 210 kg / cm2 here which designs for respective mixes were made using the procedure 211 A.C.I committee .. each test were prepared Designed four specimens initial test, which carried out the respective breaks, none of achievement Results v reach the Theoretical design strength. The necessary adjustments were made on the basis of experiences of Design and then made Again four test specimens and respective breaks, reached the final design. With design Found final 30 concrete specimens were prepared each test, breakages Cuyas Held in the manuals Press 120 Tons of Capacity and Soil Laboratory Concrete Faculty of Civil Engineering of the National University of San Martin, who S made after the statistical evaluation of the results of the breaks, I was shown that Tests conducted Were With Many efficiency and that they had met the Reaching goals TRACES Resistance theoretical design.